Improving Reading Comprehension at The Tenth Grade Students of SMAN 2 Parepare Thought Application Numbered Head Together (NHT) Learning Model - Purnama, Atmaranie Dewi (JLE: Journal of Literate of English Education Study Program, 2020)
This research discussed how the use number head together to improve thestudents’ ability in reading.This research used quasi experimental design that applied a pretest and post-testdesign. The data was analyzed by using t-test (spssprograme). The population of thisresearch was the X grade students of SMA Negeri 2 Parepare in academic year2014/2015. There were two classes, a class for experimental class and a class for controlclass. It utilized cluster random sampling technique. The number of each class was 30students. The instrument used in this research was reading test (narrative text) use ofnumber head together (Nht) learning model.The result of this research was a significant difference between experimental groupand control group. This indicates the mean score of the post-test of experimental groupwas 84,25 while that of the control group was 77,56. Moreover, maen score of pre testwas 61,50 in experimental group and 64,75 in control group ,it means that H1 wasacceptable and the statistical hypothesis of Ho was rejected. it means that Using NHTsignificant develops the students’ ability in reading.